Pengaruh E-Service Quality Dan E-Wom Terhadap Keputusan Pembelian Kosmetik di Aplikasi Soco - Fadilla Anggraini Pramudya Putri; Finisica Dwijayati Patrikha (Lembaga Pengembangan Manajemen dan Publikasi Imperium, 2021)
This study aims to explain and analyze influence E-Service Quality and E-WOM (Electronic Word of Mouth) of the purchase decision cosmatics in application SOCO by Sociolla. The total sampel is 200 respondents using the Non Probability Sampling method. For data collected using questionnaire with a ratio measurement likert scale of 10 choices, using Google Form. Data processing used multiple linear regression analysis techniques using SPSS 25 version. The results showed that E-Service Quality had significant effect on the purchase decision with a coefficient of 0,345 and E-WOM (Electronic Word of Mouth) had significant effect on the purchase decision with a coefficient of 0,358. Simultaneously E-Service Quality and E-WOM (Electronic Word of Mouth) had a significant effect on the purchase decision with a calculated F value of 207,963. Form this research is expected for further researchers and can be a marketing strategy in an e-commerce.